2005
DOI: 10.1097/01.mlg.0000177459.80574.2d
|View full text |Cite
|
Sign up to set email alerts
|

Mastoidectomy and Trans-Corneal Viral Transmission

Abstract: The incidence of chronic middle ear disease is falling in Britain, and in adults, is currently approximately 2.6% (inactive) and 1.5% (active). The incidence of HIV and hepatitis C is, however, rising. With this in mind, the chances of operating on a patient with undiagnosed infection is increasing. Operations involving the drilling or cutting of bone in patients with bloodborne communicable diseases are inherently dangerous to surgeons. In the pre-antibiotic era, many orthopaedic surgeons succumbed to infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 15 publications
4
40
0
Order By: Relevance
“…There was significant heterogeneity among the three studies and only one study was deemed clinically relevant and of adequate quality [49]. The three studies were found describing aerosolization of bone dust and contaminated irrigation fluid (Table 9) [49][50][51]. Aggregated Evidence: Grade D: three experimental studies.…”
Section: Mastoid Surgerymentioning
confidence: 99%
“…There was significant heterogeneity among the three studies and only one study was deemed clinically relevant and of adequate quality [49]. The three studies were found describing aerosolization of bone dust and contaminated irrigation fluid (Table 9) [49][50][51]. Aggregated Evidence: Grade D: three experimental studies.…”
Section: Mastoid Surgerymentioning
confidence: 99%
“…Furthermore, bony microspicules penetrate the cornea in animal models, and transconjunctival spread of COVID-19 has been reported. 57,58 For complicated otitis media or acute mastoiditis, a 24to 48-hour trial of medical management should be attempted prior to surgery. For patients with unknown, suspected, or positive COVID-19 status, myringotomy and tympanostomy tube insertion is preferred to cortical mastoidectomy for uncomplicated acute mastoiditis refractory to medical therapy.…”
Section: Audiologic Evaluation and Otologic Surgerymentioning
confidence: 99%
“…Bone scattering from temporal bone drilling can be up to 3.5 feet. 12 Powered instruments had been shown to generate blood-containing aerosols with a concentration of hemoglobin detected in the ambient air. 11 Viruses, including human immunodeficiency virus-1 (HIV-1), was demonstrated to be viable in the aerosols generated by surgical power instruments.…”
Section: To the Editormentioning
confidence: 99%